Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees. (12th December 2018) - Chu, Chengjin; Lutz, James A.; Král, Kamil; Vrška, Tomáš; Yin, Xue; Myers, Jonathan A.; Abiem, Iveren; Alonso, Alfonso; Bourg, Norm; Burslem, David F.R.P.; Cao, Min; Chapman, Hazel; et al.
Abstract: Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.